2001
DOI: 10.4269/ajtmh.2001.65.47
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Plasmodium falciparum-infected erythrocytes to soluble platelet endothelial cell adhesion molecule-1 (PECAM-1/CD31): frequent recognition by clinical isolates.

Abstract: Abstract. Platelet-endothelial cell adhesion molecule-1 or CD31 (PECAM-1/CD31) is a receptor recognized by Plasmodium falciparum-parasitized erythrocytes (pRBCs). Fluorescence-labeled soluble recombinant PECAM-1/ CD31 (sPECAM-1/CD31) is shown to bind to the surface of P. falciparum-infected erythrocytes on up to 70% of the cells. Binding is blocked by the addition of the unlabeled receptor in a dose-dependent fashion, but not by unrelated receptor-proteins. A significant correlation was found between the bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…P. falciparum as a species consists of many different strains, some of which have been shown to differ in characteristics such as rosetting, which shows a positive correlation with the severity of malaria [32]. Although P. chabaudi clone AS is normally the first choice of clone for laboratory researchers working with the P. chabaudi mouse model of malaria (it is the best-characterized P. chabaudi clone), more- or less-virulent clones can be used to tease apart the genetic and immunological mechanisms behind the virulence of malaria infection.…”
Section: Unraveling Parasite Genetics Using the P Chabaudi Mouse Modelmentioning
confidence: 99%
“…P. falciparum as a species consists of many different strains, some of which have been shown to differ in characteristics such as rosetting, which shows a positive correlation with the severity of malaria [32]. Although P. chabaudi clone AS is normally the first choice of clone for laboratory researchers working with the P. chabaudi mouse model of malaria (it is the best-characterized P. chabaudi clone), more- or less-virulent clones can be used to tease apart the genetic and immunological mechanisms behind the virulence of malaria infection.…”
Section: Unraveling Parasite Genetics Using the P Chabaudi Mouse Modelmentioning
confidence: 99%
“…Thus, while the PECAM1 interaction of parasites does appear to be mediated through PfEMP1 it is unclear if this interaction is mediated by specific sub-domains of DBL domains or if indeed the interaction is dependent on full-length PfEMP1 molecules. PECAM1 is expressed by endothelial cells, monocytes, platelets and granulocytes [11] and parasite adhesion to this receptor appears to be common (50%) among field parasites [74]. If PfEMP1 containing DC5 bind PECAM1, this does not rule out that other PfEMP1 domains or structures could convey parasites this binding phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Berger et al showed that DC5-containing PfEMP1 bound to platelet and endothelial cell adhesion molecule 1 (PECAM1) has been associated with CM [41,42]. However, the binding of IEs to PECAM1 was also found in uncomplicated malaria patients, where DC5-containing PfEMP1 was also expressed by the parasite when not selected for adhesion to brain endothelial tissue [43,44,45]. …”
Section: Cytoadherence Of Infected Erythrocytementioning
confidence: 99%